Research methodology for analyzing transformation of higher pedagogical education today - Pisareva, Svetlana A.; Tryapitsina, Alla P. (Известия Саратовского университета. Новая серия: Акмеология образования. Психология развития)
Relevance. Systemic changes in education, driven by digital transformation, necessitate the development of a methodology for studying transformative processes within the post-non-classical scientifi c paradigm. This study aims to describe the methodological foundations for qualitative research of pedagogical reality, with a focus on the subsequent application of scenario forecasting. The research employs various methods , including theoretical and discursive analysis, ranking results from a survey of teachers (N = 800) working at universities and institutes implementing teacher training programs (Volgograd, Vologda, Moscow, Omsk, St. Petersburg, Saratov, Tobolsk, Ulyanovsk), and generalization techniques. The main results. The transformation of the education sector is viewed as a systemic renewal infl uenced by external factors. The study presents the methodological framework for analyzing transformation of education, tailored to the current stage of scientifi c development and highlighting the “new” role and responsibility of researchers. It emphasizes the importance of collaborative research experiences and situates transformative processes within various university contexts. Importantly, it argues that understanding the transformation of pedagogical education cannot occur in isolation from analyzing the transformation of school education. The study demonstrates that the phenomenological approach is eff ective for identifying both objective and subjective characteristics of pedagogical reality in the course of the analysis of the transformation of pedagogical education. Pedagogical education is conceptualized as a self-organizing social system characterized by instability and dynamism, which necessitates participation in the study of all stakeholders interested in making decisions aff ecting their fate. This approach also involves the use of humanitarian expertise and scenario forecasting. By examining transformation practices in a specifi c context, researchers can select appropriate scenarios (analog, adaptive, innovative) and develop prospective assessments. Conclusions. The research methodology for studying transformation of higher pedagogical education relies on phenomenological refl ection and primarily utilizes qualitative analysis methods. It emphasizes the research team’s responsibility for scientifi c outcomes and their integration into the scientifi c community’s activities. It should be adapted to specifi c university research conditions. Practical Significance. The methodology is relevant for fostering collaborative research initiatives and developing research programs aimed at transforming pedagogical education across various universities.